Prolonged Activity Restriction After Concussion: Are We Worsening Outcomes?. (May 2016) - DiFazio, Marc; Silverberg, Noah D.; Kirkwood, Michael W.; Bernier, Raquel; Iverson, Grant L.
The current treatment of concussion or mild traumatic brain injury (mTBI) is primarily based on expert consensus. Most clinical practice guidelines advise cognitive and physical rest after injury including withdrawal from normal life activities such as school attendance, sports participation, and technology use until symptoms resolve. Some individuals who sustain an mTBI experience persistent physical, cognitive, and mental health problems. Activity restriction itself may contribute to protracted recovery and other complications. Williamson's Activity Restriction Model of Depression, formulated more than 20 years ago, is central to this hypothesis. We review research evidence for potential harms of prolonged activity restriction and report an mTBI case as an example of how an "activity restriction cascade" can unfold. According to this model, psychological consequences of removal from validating life activities, combined with physical deconditioning, contribute to the development and persistence of postconcussive symptoms after mTBI in some youth. A modification to mTBI guidelines that emphasizes prompt reengagement in life activities as tolerated is encouraged.